MARKETING STRATEGIES OF MULTINATIONAL COMPANIES FOR FOREIGN MARKETS (Лучшие интеллектуальные исследования, 2025)
Abstraсt: This article presents a number of analytical data on marketing strategies and marketing research practices of transnational companies for foreign markets.